Dynamic modelling and control of mass spring system with large load uncertainty - Aizuddin, Abdul Rahim (2008)
In this study, we introduce MATLAB software package for modelling, simulating and analyzing dynamic systems. The purpose of this project is to construct modelling of a mass spring system with a linear control design which is the Proportional Integral Derivatives (PID). To evaluate the performance of this system, PID is chosen as a control strategy and will be compared with the uncontrolled by performing a MATLAB Simulink® simulation. This illustrate the use of Simulink® which concern of modelling and simulating of engineering systems. This system can be divided into two sections which are to obtain the equivalent transfer function of the model and to obtain the control of the model’s output. The purpose of the controller is to control the output so it will be in specific condition that it’s required. All of this system is implemented in MATLAB Simulink®.